Understanding the role of metastasis-associated lung adenocarcinoma transcript 1 (malat1) long non-coding RNA during zebrafish retina regeneration - SHARANYA. P (My University, 2025)
Lower vertebrates can regenerate most organs, including the central nervous system (CNS), while mammals typically form scars instead. The retina, part of the CNS, can regenerate efficiently in lower vertebrates, inspiring research in mammalian retina regeneration. Although growth factors and epigenetic modulation can induce some regeneration in mammals, it's limited. This research could lead to therapies for vision impairment, which still is an unmet clinical need. In zebrafish, Müller glia (MG) cells respond to injury by reprogramming into progenitor cells (MGPCs), which proliferate, migrate, and differentiate accordingly to replace damaged neurons. Molecular mechanisms behind this involve numerous signalling pathways and epigenetic changes. Long non-coding RNAs (lncRNAs), such as malat1, play crucial roles in this process. malat1 is highly deregulated in cancers and is essential for zebrafish development but dispensable in mice. malat1 is upregulated immediately after retinal injury in zebrafish, much like immediate early genes (IEGs). It primarily acts in neighboring cells, through the Notch signalling pathway. After injury, malat1 expression increases in cells adjacent to the proliferating Müller glia (MG) cells. This induces the expression of the Notch ligand, delta d (dlld). dlld interacts with Notch receptors on proliferating MG cells, leading to the activation of Notch signalling. Notch signalling induces the expression of her4.1 in proliferating MG cells. her4.1 then induces expression of pro proliferative genes like egr1, in these cells. Egr1 is a transcription factor known to promote cell proliferation by inducing cell cycle genes such as cdk4 and xv ccnd2 while suppressing cell cycle inhibitors like cdkn1. Knockdown of malat1 results in decreased egr1 levels, and thus may regulate MGPC proliferation. The level of egr1 is further enhanced in proliferating cells by Wnt signalling. Stabilization of β-catenin, a key component of the Wnt pathway, increases egr1 levels, by directly acting on its promoter. malat1 and Wnt signalling independently induce egr1, creating a synergistic effect that drives proliferation during retina regeneration. TGF-β signalling exerts different effects on proliferation in zebrafish and mice through its regulation of malat1 via another lncRNA, talam1. In zebrafish, TGF-β signalling inhibits malat1 expression by downregulating talam1, which was necessary for stabilizing malat1. Conversely, in mice, TGF-β signalling upregulates Talam1, stabilizing Malat1 and enhancing its expression. However, the overall impact of TGF-β signalling on cell proliferation remains complex because of its interactions with various signalling molecules. Both TGF-β1 and Egr1 are pro-proliferative individually, but their interaction can inhibit each other's function. This may occur because the TGF-β signalling effector pSmad3 physically binds with Egr1, preventing each from targeting their respective loci and thereby inhibiting proliferation. In summary, this study highlights the pro proliferative role of malat1 in retina regeneration, and its differential regulation in zebrafish and mice, opening new avenues for exploring its therapeutic potential.
Keywords: RNA; zebrafish